Circadian system: neural network with suprachiasmatic nucleus at the top of a hierarchical organization - Stanojlović, Olivera P; Šutulović, Nikola B (Medicinski podmladak, 2018)
Biological rhythms represent series of events occurring repeatedly in the same order and time intervals in all living beings including humans. All eukaryotes show variabilities in the genetic (rhythm of DNA and RNA synthesis, mitosis rhythm), biochemical (metabolic rhythms) and physiological (rhythm of synthesis and secretion of certain hormones, menstrual cycle, rhythmic body temperature changes, heart rate, breathing frequency, the sleep/wake cycle, work and rest, etc.) functions by enhancing and reducing their activities throughout cycles. Circadian oscillator genesis is based on combination of negative feedbacks, clock gene expression and translation of proteins that control temporal sequences of cell metabolic processes. Clock genes have been discovered: per (periodic) and tim (timeless), and they encode the information for synthesis of two proteins named the same as previously mentioned genes. These proteins accumulate in the cell during the night and degrade during day. Their concentration oscillates in 24h long cycles, synchronously with the circadian rhythm. For this discovery, American scientists received a Nobel Prize in Physiology or Medicine in 2017. With excellent precision, our internal clock regulates critical functions such as behavior, hormone secretion, sleep, body temperature, metabolism, and other functions. By doing this they adjust the physiological functions to different stages of the day, increase the activity of SCN neurons that regulate wakefulness / slow wave sleep and control the endogenous clock. The pineal gland is in direct contact with the endogenous clock and produces hormone melatonin that causes drowsiness. The melatonin concentration is decreased or is not measurable during the day. Light, pineal gland and melatonin regulate the sleep cycle, and each disturbance of this components leads to dysfunctions. Key words: biological rhytms, endogenous clock, pineal gland, melatonin